Recent Updates on Intelligent System for Talent Management: Does That Become a Helpful System? - Aditia Putra Hamid; Rosyid Ridlo Al-Hakim; Yanuar Zulardiansyah Arief; ‪Brainvendra Widi Dionova; Mahmmoud Hussein A. Alrahman (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
The use of information technology in human management today has increased, along with the implementation of intelligent systems that generally use artificial intelligence (AI) in their application. One of the areas of human management that has adopted AI is talent management (TM). TM is crucial for companies to identify, manage, determine, assess, and recommend talent (in this case, it can be employees) for their company's sustainability. The application of family planning in TM is not as extensive as thought, but this study tries to review the latest research that adapts AI to a very complex TM process. The results of this review are at least 11 articles involved in the use of family planning. These 11 articles certainly discuss one or more processes in TM, such as talent identification, talent matching or mapping, and talent recommendations. Some critical studies in the future are that in practice, AI needs to be widely used, especially to handle large-scale data management (data intelligence), in addition to intelligent system methods, and AI can be used for all processes in TM, proven to be accurate, efficient, safe, and fast in practice.